2021
DOI: 10.1111/jcal.12618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digital games on student motivation in mathematics: A meta‐analysis in K‐12

Abstract: Background: Motivation is an important factor in the learning process and supporting students' motivation in mathematics is a significant challenge for educators.Educational technologies, such as digital games, offer potential for engagement in mathematics learning activities.Objectives: To contrast the general decrement in student motivation in mathematics, a multilevel meta-analysis was carried out to synthesize the results of studies concerning the impact of digital games on K-12 student motivation in mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 89 publications
3
22
0
1
Order By: Relevance
“…In this study, students' EL decreased and GL increased but correlation between EL and GL was not observed, indicating that the personalized RPG environment constructed in this study has the potential of motivating students and promote sufficient GL investment in efficient learning. This echoes previous empirical studies (e.g., Fadda et al, 2022;Westera, 2019;Yu et al, 2021) as well as related theoretical discussions regarding motivational effects on cognitive load proposed by Paas et al (2005). These findings also align with the cognitive load theory (Kalyuga, 2009;Sweller, 2010Sweller, , 2020 that IL is determined by the learning content and cannot be altered by instructional design.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, students' EL decreased and GL increased but correlation between EL and GL was not observed, indicating that the personalized RPG environment constructed in this study has the potential of motivating students and promote sufficient GL investment in efficient learning. This echoes previous empirical studies (e.g., Fadda et al, 2022;Westera, 2019;Yu et al, 2021) as well as related theoretical discussions regarding motivational effects on cognitive load proposed by Paas et al (2005). These findings also align with the cognitive load theory (Kalyuga, 2009;Sweller, 2010Sweller, , 2020 that IL is determined by the learning content and cannot be altered by instructional design.…”
Section: Discussionsupporting
confidence: 89%
“…Apart from gaining knowledge and skills, studies also reported improvement in motivation and interest in mathematics (Higgins et. al., 2019 ; Fadda et al, 2022 ) and increased positive achievement emotions towards several subjects during interventions using educational games (Lei et al, 2022a ). Chen et al ( 2022a ) also reported a small but positive effect of digital health approaches in bullying and cyberbullying interventions with K-12 students, demonstrating that technology-based approaches can help reduce bullying and related consequences by providing emotional support, empowerment, and change of attitude.…”
Section: Resultsmentioning
confidence: 99%
“…Research on how digital tools influence students’ outcomes is part of a relevant and growing stream of academic literature. The possibilities offered by technology in the educational setting are multiple: game-based activities [ 23 ], virtual laboratories [ 24 ] or computed-based scaffolding [ 25 ] represent only a small fraction of possible applications. Due to the diversity in the available digital tools, evidence on the effectiveness in terms of students’ outcomes is mixed, usually showing positive but modest effects [ 26 ].…”
Section: Relevant Literaturementioning
confidence: 99%